PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUASAN KONSUMEN AIR MINERAL KESEHATAN HEXAGONAL Q TARAS DALAM PERSPEKTIF MANAJEMEN PEMASARAN PENDIDIKAN : (Studi Kasus Di CV Air Mineral Kesehatan Hexagonal Q-Taras Jombang) - Hanif Fazuan Qodri (As-Sulthan Journal of Education, 2025)
This study aims to analyze the influence of product quality, price, and promotion on consumer satisfaction at CV Air Mineral Kesehatan Hexagonal Q-Taras in Jombang. A quantitative approach with a survey method was employed, involving 100 respondents. Data analysis techniques included validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results indicate that product quality, price, and promotion have a positive and significant effect on consumer satisfaction, both partially and simultaneously